MO685PRESENCE OF SARS-COV-2 ANTIBODIES IN SPENT PERITONEAL DIALYSATE. (29th May 2021) - Wang, Xiaoling; Grobe, Nadja; Patel, Amrish; Uribarri, Jaime; Kotanko, Peter
Abstract: Background and Aims: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) elicits cellular and humoral immune responses. In patients with coronavirus disease 2019 (COVID-19), IgM, IgA, and IgG antibodies against SARS-CoV-2 emerge within a few days and can be detected in several body fluids, such as serum and oral fluids. End Stage Kidney Disease patients are especially vulnerable in this pandemic as they are immunocompromised, putting them at higher risks of infection and impaired response to vaccines. While repeated blood draws in hemodialysis patients pose no substantial medical or logistic problems, the situation is different in those treated by peritoneal dialysis. To overcome that limitation, we explored the presence or absence of SARS-CoV-2 antibodies in spent peritoneal dialysate in patients treated with acute and chronic peritoneal dialysis, respectively. Method: We analyzed spent PD dialysate samples from four distinct patient groups, namely Pre-Covid-19 controls (Group 1; 15 samples collected between May 2019 and Feb 2020), Covid-19 negative controls during ongoing pandemic (Group 2; 33 samples collected between March and September 2020); chronic PD patients with confirmed Covid-19 (Group 3; 30 samples collected between March and September 2020, ); and patients with confirmed Covid-19 and acute kidney injury treated with acute PD (Group 4; 18 samples collected in April 2020). SARS-CoV-2 IgG titer in spent PD dialysate was measured by enzyme-linked immunosorbent assay (ELISA) targeting Nucleocapsid (N) protein of SARS-CoV-2 virus (MPBIO cat#: 08440100). Total SARS-CoV-2 antibodies (IgG, IgM, and IgA) were measured using ELISA targeting recombinant N Protein and Spike protein (S Protein) (AFFYPRO Cat#: EA821). Absolute IgG concentration was calculated using IgG standard provided by the MPBIO ELISA kit. The total antibody titer was calculated as a relative value to the mean of antibody levels of COVID-19 negative patients. To account for different dialysate and ultrafiltration volumes, antibody titers were also normalized to total protein concentrations in the spent dialysate samples. The ratio of IgG or total antibody to total protein reflects the normalized titer. Results: Normalized anti-SARS-CoV-2 IgG titer in the four groups is illustrated in Figure 1A . The mean IgG/protein levels in Group 3 and Group 4 are 86-fold (p=0.023) and 220-fold (p=0.0003), respectively, above the mean IgG/protein levels in COVID negative patients (Group 1 and 2 combined). The discrimination between patients with and without COVID-19 is excellent (AUC 0.938). At a threshold of 0.0024%, the sensitivity and specificity are 89.6% and 97.9%, respectively (Figure 1B ). Using same threshold as Figure 1B, in Group 3, 9 out of 11 patients had a positive IgG response in all samples. In 5 patients, IgG levels decreased over time. The mean normalized total antibody/protein levels in Group 3 and Group 4 are 7.3-fold and 24-fold above those in COVID negative patients (combined Group 1 and 2; both p<0.001). Distribution pattern, ROC analysis, and dynamic change over time of total SARS-CoV-2 antibodies are like those of IgG (Figure 1D-F ). Conclusion: Covid-19 serology tests can provide much information including diagnosis, immune response, local seroprevalence, et al. Currently, most of serology tests are done using blood-related specimens. To our knowledge, this is the first study reporting SARS-CoV-2 antibodies in spent PD dialysate. Presence of SARS-CoV-2 antibodies in spent PD dialysate of peritoneal dialysis patients potentially provides a new way to perform frequent serology tests for this high-risk group. As USA is moving fast on national vaccination at this moment, using test strip developed for PD effluent to quickly and frequently check SARS-CoV-2 antibody in PD effluent could be used to monitor the vaccination efficiency while avoiding clinic visit.